(untitled) (Global Journal of Human-Social Science, 2023)
The purpose of this study is to apply exploratory factor analysis and Partial least square Structural equation to analyze the factors contributing thriving of online shopping through social media in Tanzania Seven areas of Social and Economic factors social media behavior factors Buying and Shopping Behavior Technology Internet Acceptance factors Security and Risk assessment factors Customer care pre-purchasing and Post Purchasing service and Cost factors were theoretical conceptualized to construct latent factors An online questionnaire was used as a data collection tool with 344 participants and data were analyzed using R software for statistical analysis and Smart PLS software for partial least square modeling Exploratory factor analysis was used to evaluate variable factor loadings and variables with more than or equal to 0 3 loadings were used in structural equation modeling Nine hypotheses were created with direct and indirect effect results reveled social-economic factors technology and internet adoption and Security and Risk influence social media shopping behavior This study also finds multiclonality influence between factors as social and economic and security factors influence technology adoption